2016
DOI: 10.1103/physrevb.93.245159
|View full text |Cite
|
Sign up to set email alerts
|

Rashba-Dresselhaus spin-splitting in the bulk ferroelectric oxideBiAlO3

Abstract: It has been recently suggested that the coexistence of ferroelectricity and Rashba-like spin-splitting effects due to spin-orbit coupling in a single material may allow for a non-volatile electric control of spin degrees of freedom. In the present work, we compared the structural and ferroelectric properties of tetragonal and rhombohedral phases of ferroelectric BiAlO3 by means of densityfunctional calculations. In both phases, we carefully investigated Rashba and Dresselhaus effects, giving rise to spin-split… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
46
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(49 citation statements)
references
References 59 publications
1
46
1
Order By: Relevance
“…When including the SOI in the ferroelectric phase, we now observe several splittings of the "oxygen hole bands" located above the Fermi level E F (see their degeneracy is lifted according to the spin direction as illustrated by Figure 3.b. Looking at spin textures in the (k x ,k y ) plane represented in Figures 3.d and 3.e, we clearly observe two energy contours with clockwise (outer contour) and counter-clockwise (inner contour) [17] or in heavy metals such as (111) oriented Bi [26]. We now turn our attention to possible functionalization of the Rashba interaction in this ferroelectric material.…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…When including the SOI in the ferroelectric phase, we now observe several splittings of the "oxygen hole bands" located above the Fermi level E F (see their degeneracy is lifted according to the spin direction as illustrated by Figure 3.b. Looking at spin textures in the (k x ,k y ) plane represented in Figures 3.d and 3.e, we clearly observe two energy contours with clockwise (outer contour) and counter-clockwise (inner contour) [17] or in heavy metals such as (111) oriented Bi [26]. We now turn our attention to possible functionalization of the Rashba interaction in this ferroelectric material.…”
mentioning
confidence: 73%
“…Moreover, they can also accommodate heavy elements, an important aspect for SOI based applications. So far, BiAlO 3 has been proposed theoretically to be the first oxide exhibiting ferroelectricity and Rashba physics [17] -although this coexistence was already observed in the semiconductor GeTe [16]. While BiAlO 3 harbors a heavy element and a large ferroelectric polarization -estimated around 90 µC.cm −2 -, the computed Rashba coefficient α R remains relatively moderate -around 0.39 and 0.74 eV.Å-although comparable to conventional systems such as (111) oriented Bi [26].…”
mentioning
confidence: 99%
“…It shows an improved performance of ferromagnetism, that the magnetic moment of the BAO/LSMO heterostructure distinctly increases compared to the single LSMO layer, while a complete opposite phenomena compared to the BFO/LSMO heterostructure. [28] As reported in previous theoretical literature, [16] a spin-splitting was predicted to occur around the conduction band minimum, because of the Rashba-type spin-orbit coupling (SOC) effect in BAO tetragonal www.advancedsciencenews.com www.pss-rapid.com phase. It will strongly impact on the magneto-transport property of LSMO, leading to the stronger magnetic interaction at the BAO/LSMO interface.…”
mentioning
confidence: 83%
“…Very recently, we analyzed the temperature dependence of conduction mechanism of BAO thin films . Notably, Silveira et al theoretically indicated that BAO could exhibit a coexistence of ferroelectricity and Rashba‐type spin splitting effect. Hence, the BAO‐based oxide heterostructures may initiate many considerable and fancy interface and surface effects, e.g., for the improved magnetic moment and the two‐dimensional electron gas (2DEG) at interfaces, which is the motivation behind our work.…”
mentioning
confidence: 99%
“…Very large SOC (~10 2 -10 3 meV) has been predicted, resulting from a polarization-induced potential gradient. [36][37][38][39][40][41][42][43] In addition to the sizable SOC favorable for the experimental demonstration of the TAMR effect, these materials have the advantage of the reversible FE polarization which can be switched by an applied electric field. Since FE materials are non-centrosymmetric, the spin-momentum coupling linear in wave vector k is allowed by symmetry, giving rise to the linear Rashba and Dresselhaus SOC in bulk of these compounds.…”
Section: Introductionmentioning
confidence: 99%